(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
In the context of ongoing banking transformation driven by digitalization, regulatory reforms, and increasing financial risks, ensuring the quality of banks’ credit portfolios has become a critical priority for financial stability and sustainable economic development. This study examines the key directions and mechanisms for improving credit portfolio quality under conditions of structural and institutional transformation in the banking sector. The research focuses on the impact of modern risk management systems, credit assessment technologies, portfolio diversification strategies, and regulatory compliance on credit portfolio performance. Particular attention is paid to the role of digital credit scoring models, early warning systems, and non-performing loan management practices in reducing credit risk and enhancing asset quality. Using analytical and comparative methods, the study evaluates existing approaches to credit portfolio management and identifies their limitations in the context of transitional banking systems. The findings demonstrate that improving credit portfolio quality requires an integrated approach combining technological innovation, institutional reforms, enhanced supervision, and strategic credit policy adjustments. The results of the study contribute to the development of practical recommendations for commercial banks and policymakers aimed at strengthening financial resilience, increasing credit efficiency, and supporting long-term economic growth in transforming banking environments.